Low-dose PD-1 inhibitor combined with lenvatinib for preemptive treatment of recurrence after liver transplantation for hepatocellular carcinoma: Case report and literature review - Jin, Xin; Zhang, Kangjun; Fang, Taishi; Zeng, Xinchen; Yan, Xu; Tang, Jianxin; Liang, Ziming; Xie, Linjie; Zhao, Dong (Frontiers in Oncology, 2022)
Orthotopic liver transplantation (OLT), as one of the curative methods for the treatment of hepatocellular carcinoma (HCC), has brought hope to patients with HCC. However, treatment options for HCC recurrence and metastasis after liver transplantation are limited. Immune checkpoint inhibitor (ICI), such as programmed cell death protein 1 (PD-1) inhibitor, have been successfully used in advanced or metastatic HCC, but the data on the safety of PD-1 inhibitor after liver transplantation is limited. In this article, we report a 47-year-old patient with acute-on-chronic liver failure and multiple HCC who was successfully treated with liver transplantation. On the 45th day after OLT, the patient’s alpha fetoprotein (AFP) and lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) were increased, and imaging examination showed no residual tumor. The patient had high risk factors for tumor recurrence before operation, so the possibility of tumor recurrence was considered. When the tumor markers showed an upward trend, we immediately treated the patient with lenvatinib 8 mg, after half a month, the AFP and AFP-L3 continued to increase compared with before. Then we used low-dose nivolumab 40mg, the patient’s AFP and AFP-L3 gradually decreased. One month later, a second low-dose nivolumab 40mg was given, and the patient’s tumor markers gradually decreased to normal. No acute rejection and other complications occurred during the treatment. So far, we have followed up this patient for 2 years, and no tumor recurrence was observed. To our knowledge, this is the first reported case using a low dose of nivolumab in combination with lenvatinib to prevent recurrence of HCC after liver transplantation.